(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the structural-semantic analysis of the lexeme “Foot/Oyoq” in two unrelated languages – English and Uzbek in a cross-sectional aspect, using the method of component analysis. As a result of research, the composition of the “foot/oyoq” sememes was determined in a hierarchical order and, as a result, peripheral and potential semes were managed to identify. Semantic analysis of the lexemes “foot/oyoq” is considered to be as a necessary step in solving problems associated with their study as a polysemantic word.